Advances in distributed agent-based retrieval tools - Pallotta, Vincenzo; Soro, Alessandro; Vargiu, Eloisa (Studies in computational intelligence, 2011)
This volume contains revised and extended versions of papers presented at the 4th edition of the international workshop on Distributed and Agent-based Retrieval Toos (DART'10) held in June 2010, in conjunction with the Symposium on Human Language Technology for the Information Society, in Geneva, Swizerland. Practitioners and researchers working on pervasive and intelligent access to web services and distributed information retrieval met to share their results and insights in intriguing and challenging topics such as: (i) social media and collaboration, (ii) new challenges in search technology, (iii) sentiment analysis and opinion mining, (iv) distributed information retrieval, (v) pervasive intelligence. Every chapter, before discussing in depth the specific topic, presents a comprehensive review of related work and state of the art, in the hope of this volume to be of use in the years to come, to both researchers and students.